Performance Costs and Benefits of Collective Turnover: A Theory-Driven Measurement Framework and Applications - Nick Zubanov; Elena Shakina (Institute of Labor Economics (IZA), 2023)
Building on job matching theory, we model the effect of collective turnover on workplace performance as the total of its costs from operational disruptions and benefits from better job-worker match quality, each component varying with turnover level. The resulting theoretical turnover-performance relationship is generally curvilinear, nesting all the hitherto known patterns – linear, "U-shape" and "inverted U-shape" – as special cases, and lends itself to an empirically estimable regression model from which one can derive the implied costs and benefits of turnover. Applications to data from two retail firms reveal some benefits from turnover in one firm, and none in the other. Turnover costs exceed benefits in both firms.
Keywords: J63; 330; employee turnover; performance